Developing a globally applicable evidence-informed competency framework to support capacity strengthening in clinical research. Issue 2 (30th March 2017) - Julé, Amélie; Furtado, Tamzin; Boggs, Liam; van Loggerenberg, Francois; Ewing, Victoria; Vahedi, Manhaz; Launois, Pascal; Lang, Trudie
Abstract : Capacity development for clinical research is held back by a lack of recognition for the skills acquired through involvement in clinical trials and in other varied types of global health research studies. Although some competency frameworks and associated recognised career pathways exist for different clinical research roles, they mostly apply to a single role or study setting. Our experience supports the need for an integrated approach, looking at the many roles in parallel and at all types of clinical research beyond trials. Here, we propose a single, flexible framework which is applicable to the full global health research team, and can be used for recognising staff by highlighting acquired skills and possible progression between various roles. It can also illuminate where capacity needs strengthening and contribute to raising research engagement. Through systematic analysis of existing competency frameworks and current job descriptions covering 11 distinct, broad clinical research roles, we identified and defined 50 key competencies required by the team as a whole and throughout the study life cycle. The competencies are relevant and adaptable to studies that differ in design, geographical location or disease, and fall in five main areas—(1) Ethics, Quality and Risk Management; (2) Study and Site Management; (3) Research Operations; (4) Scientific Thinking; and (5) Professional Skills. A pilot framework and implementation tools are now available online and in paper format. They have the potential to be a new mechanism for enabling research skills development and career progression for all staff engaged in clinical research globally.